2012
DOI: 10.1093/mutage/ges006
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual variation in G2 chromosomal radiosensitivity

Abstract: Intra-individual variation in G(2) chromosomal radiosensitivity was examined by repeatedly taking blood samples from two individuals. Two healthy female volunteers provided a total of 44 blood samples, Donor 1 gave 28 samples in four time periods between 2001 and 2006 and Donor 2 gave 16 samples in two of the same time periods. Lymphocytes were cultured for 72 h prior to irradiation with 0.5 Gy, 300 kV X-rays. Colcemid was added 30 min post-irradiation. Cultures were harvested 90 min post-irradiation and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This suggests a hormonal effect on radiation response, which appears reasonable considering the synergistic mechanisms described above. Intra-individual response specifically in G2 chromosomal radiosensitivity has also previously been reported by many groups including ours without any obvious contributory factors like ADT in this study [ 31 , 41 , 42 ]. These studies suggest that multiple sampling from the same donor should be considered, although this is often not practical for patient donors.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests a hormonal effect on radiation response, which appears reasonable considering the synergistic mechanisms described above. Intra-individual response specifically in G2 chromosomal radiosensitivity has also previously been reported by many groups including ours without any obvious contributory factors like ADT in this study [ 31 , 41 , 42 ]. These studies suggest that multiple sampling from the same donor should be considered, although this is often not practical for patient donors.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis was supported by a study demonstrating the Mendelian heritability of chromosomal radiosensitivity in family members of breast cancer cases [ 147 , 148 ]. Later, strong evidence for heritability of the G 2 radiosensitive phenotype was confirmed in another cohort [ 149 ].…”
Section: Review Of Existing Studiesmentioning
confidence: 93%
“…A compilation of data from such studies is beyond the scope of current review. However, one important issue is the intra-individual variations of G 2 which were investigated in a special study [ 149 ]. The heterogeneity was so significant that the authors concluded that too much reliance should not be placed on the result from a single sample when assessing individual radiosensitivity status by the G 2 assay.…”
Section: Review Of Existing Studiesmentioning
confidence: 99%
“…Nowadays, low-dose radiation and its effect (not immediately noticeable) is a leading topic because of the problems with collecting reliable data and its long-term biological consequence [ 2 ]. As with sensitivity to sunlight or to chemotherapeutic drugs, sensitivity to ionizing radiation shows variation among individuals [ 3 ]. It has been shown that radiosensitivity is a heritable trait of our organisms shaped by environmental factors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%